Changes in SOFC Cathode Crystallographic Structure Induced by Temperature, Potential and Oxygen Partial Pressure Studied Using in-Situ HT-XRD. (2nd June 2015) - Kivi, Indrek; Aruväli, Jaan; Kirsimäe, Kalle; Heinsaar, Alar; Nurk, Gunnar; Lust, Enn
Abstract : Porous and monolithic La0.6 Sr0.4 Co3 −δ, Gd0.15 Sr0.85 CoO3 −δ and La0.6 Sr0.4 MnO3 −δ cathodes for intermediate temperature solid oxide fuel cell applications have been studied at different cathode potentials and at different oxygen partial pressures using high-temperature in situ XRD (HT-XRD) method. The kinetic response of the crystallographic structure and lattice parameters on the changes of electrode potential has been correlated with the chronoamperometric data and discussed. Reversible changes in the lattice parameters were observed depending on the temperature ( T ), electrode potential ( E ) and oxygen partial pressure ( p O2 ) applied. At fixed T and p O2, the cathode potential noticeably influences the unit cell volume, thus, the oxygen stoichiometry and concentration of vacancies. The La0.6 Sr0.4 MnO3 -δ cathode does not have remarkable crystallographic changes under comparable conditions. Influence of the cathode potential on the unit cell volume was more pronounced at lower p O2 .